2013
DOI: 10.1080/15374416.2013.814544
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Anxiety and Depression in Children and Adolescents: Evidence From Event-Related Brain Potentials

Abstract: The current study, which was a reanalysis of previous data, focused on the error-related negativity (ERN)-an event-related potential (ERP) associated with error monitoring-and the feedback negativity (FN)-an ERP associated with reward processing. Two objectives motivated this study: first, to illustrate the relationship between the ERN and anxious symptoms, and the relationship between the FN and depressive symptoms; second, to explore whether the ERN and the FN relate uniquely to anxiety and depression, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
81
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 97 publications
15
81
2
1
Order By: Relevance
“…Previous studies have found an attenuated RewP during a gambling task in individuals with high relative to low trait-like anxiety (Gu, Huang, & Luo, 2010;Lange, Leue, & Beauducel, 2012) and obsessive-compulsive symptoms (Simons, 2010). However, one study found that negative emotionality was associated with an enhanced RewP (Santesso et al, 2012) and other studies have found no association between anxiety and the RewP (Bress, Meyer, & Hajcak, 2013). In this study, internalizing symptoms (anxiety, depression, stress, and worry) were not associated with the RewP across either the predictable or unpredictable context.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies have found an attenuated RewP during a gambling task in individuals with high relative to low trait-like anxiety (Gu, Huang, & Luo, 2010;Lange, Leue, & Beauducel, 2012) and obsessive-compulsive symptoms (Simons, 2010). However, one study found that negative emotionality was associated with an enhanced RewP (Santesso et al, 2012) and other studies have found no association between anxiety and the RewP (Bress, Meyer, & Hajcak, 2013). In this study, internalizing symptoms (anxiety, depression, stress, and worry) were not associated with the RewP across either the predictable or unpredictable context.…”
Section: Discussioncontrasting
confidence: 47%
“…The current study sheds new light on the nature of reward dysfunction in MDD in three ways: First, building upon past ERP research in non-clinical samples (Bress, Meyer, et al, 2013; Bress et al, 2012; Foti & Hajcak, 2009) and replicating a recent report from a clinical sample (W. H. Liu et al, 2014), MDD was associated with reduced reward-related neural activity, as indicated by FN amplitude. Second, we found converging evidence across ERP and fMRI measures, such that FN amplitude and VS activation to reward were correlated within the MDD group.…”
Section: Discussionmentioning
confidence: 53%
“…Notably, blunted FN amplitude is associated with MDD symptoms in both clinical (W. H. Liu et al, 2014) and nonclinical samples (Bress, Smith, Foti, Klein, & Hajcak, 2012; Foti & Hajcak, 2009), an association which appears to be specific to symptoms of MDD and not anxiety (Bress, Meyer, & Hajcak, 2013). Blunted FN amplitude may represent a neurobiological mechanism of risk for MDD, such that it is more pronounced among individuals with a family history of MDD (Foti, Hajcak, Kotov, & Klein, 2011) and has been shown to prospectively predict first episode onset of MDD over and above other known risk factors (Bress, Foti, Kotov, Klein, & Hajcak, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize, however, that the conceptual issues apply to all psychophysiological studies that correlate individual difference measures with subtraction-based difference scores-a practice that is actually quite common. For instance, recent studies in emotion often subtract neutral from emotional condition averages to quantify individual differences in emotional reactivity (Angus, Kemkes, Schutter, & Harmon-Jones, 2015;Bress, Meyer, & Hajcak, 2015;Burkhouse, Siegle, Woody, Kudinova, & Gibb, 2015;Hoenen, L€ ubke, & Pause, 2015;Kornilov, Magnuson, Rakhlin, Landi, & Grigorenko, 2015;McTeague, Lang, Laplante, & Bradley, 2011;Meyer, Hajcak, Torpey-Newman, Kujawa, & Klein, 2015;Sylvester, Hudziak, Gaffrey, Barch, & Luby, 2015). Indeed, current recommendations from experts in the field involve "isolating components of interest by creating [subtraction-based] difference waves" (Luck, 2014).…”
mentioning
confidence: 99%